Morphological responses of three contrasting Soybean (Glycine max (L.) Merrill) genotypes under different levels of salinity stress in the coastal region of Bangladesh - Ahmed, Rayhan; Islam, Md. Morshedul; Sarker, H. M. Moin Uddin; Hasan, Mehedi; Hossain, Md. Rakib; Shila, Akhinur; Ahammed, Rayhan (Journal of Plant Stress Physiology, 2023)
Soil salinity, a global environmental issue, inhibits plant development and production. Soybean is an economically important legume crop whose yield and quality are highly affected by excessive levels of salt in the root zone. A factorial experiment was conducted in a net house from October 2019 to January 2020 to evaluate the performance of three distinct soybean genotypes under varying levels of salinity stress. The experiment followed a completely randomized design (CRD) with three replications. Three soybean cultivars, namely BINA Soybean 1, BINA Soybean 2, and BINA Soybean 4 were used in this experiment. The soil salinity treatments were 0 mM NaCl, 50 mM NaCl, 100 mM NaCl, 150 mM NaCl, and 200 mM NaCl. The electrical conductivity (EC) of the soil sample was 0.91dS/m. Six seeds were sown 3 cm deep in each pot. A total of 45 pots were used in this experiment. The performance of each variety was evaluated based on its germination percentage, time of germination, no. of branches/plant, no. of leaves/plant, no. of flowers/plant, plant height (cm), no. of pods/plant, pod length (cm), seeds/pod, and root length (cm). Based on the results obtained from this research trial, it can be inferred that the BINA Soybean 2 variety along with 0 mM NaCl, 50 mM NaCl, and 100 mM NaCl treatments exhibited superior performance in all parameters compared to the other varieties. This study provides clear evidence that the soybean, particularly the BINA Soybean 2 variety, holds significant promise as a crop suitable for coastal regions. Furthermore, it suggests that the cultivation of soybeans in such areas could potentially enhance agricultural productivity, particularly in the presence of mild saline conditions. Nevertheless, it exhibits limited growth potential in environments with elevated salinity levels.